THE CHANGES NUMBER OF FIBROBLAST IN THE TOOTH EXTRACTION WOUND HEALING TREATED WITH GARLIC EXTRACT - Irawan, Rudi; Prameswari, Chika Kencana; Dianawati, Nur; Rahmawan, Dzanuar (Indonesian Journal of Dentistry, 2024)
Background: Fibroblast has an important role in the process of wound healing. Garlic (Allium sativum) is a plant that is widely consumed in the world and contains compounds that have potential in the wound healing process. This research aims to see changes in the number of fibroblast in the wound healing process after tooth extraction with treated garlic extract.Method: This research was laboratory experimental with a posttest control-only group design. The number of samples in this research was 28 rats which were divided into 4 groups, without treated extract (control); with garlic extract 20%, 40%, 80%.Result: Based on the results of the analysis with the Kruskal Wallis test, this shows that there was a significant difference between each group, with a significant p-value of 0.00 (p <0.05).Conclusion: This research found that the number of fibroblasts was higher in the group given garlic extract..